Perancangan Robot Penyiraman pada Tanaman Tomat Beef (Lycopersicum esculentum Mill) menggunakan Metode Forward Chaining - Baginda siregar; Daren Sulistio (Informatics Engineering, Faculty of Computer Science, 2026)
Plants, especially tomatoes, have high economic value and require regular maintenance, especially watering, to maintain optimal growth. This study developed an automatic tomato plant watering robot named